2022
DOI: 10.1021/acs.inorgchem.2c00149
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Integrated Desulfurization from Natural Gas over Zn-ZIF-Derived Hierarchical Lamellar Carbon Frameworks

Abstract: Selective removal of carbonyl sulfide (COS) and hydrogen sulfide (H 2 S) is the key step for natural gas desulfurization due to the highly toxic and corrosive features of these gaseous sulfides, and efficient and stable desulfurizers are urgently needed in the industry. Herein, we report a class of nitrogen-functionalized, hierarchically lamellar carbon frameworks (N-HLCF-xs), which are obtained from the structural transformation of Zn zeolitic imidazolate frameworks via controllable carbonization. The N-HLCF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Zhang et al reported a series of nitrogen-functionalized hierarchically lamellar carbon frameworks (N-HLCF-xs), which showed a high density of nitrogen base sites (17.52 wt %) and pyridine ratio (59.91%) with a large BET surface area (645−923 m 2 /g). 121 As an efficient and multifunctional desulfurizer for the removal of H 2 S and COS, the N-HLCFxs displayed nearly 100% COS and H 2 S conversion at 70 and 120 °C, respectively. Long's group synthesized N-doped mesoporous carbon by using a traditional colloidal silica nanocasting technology (Figure 3c).…”
Section: Carbon-based Materialsmentioning
confidence: 97%
See 4 more Smart Citations
“…Zhang et al reported a series of nitrogen-functionalized hierarchically lamellar carbon frameworks (N-HLCF-xs), which showed a high density of nitrogen base sites (17.52 wt %) and pyridine ratio (59.91%) with a large BET surface area (645−923 m 2 /g). 121 As an efficient and multifunctional desulfurizer for the removal of H 2 S and COS, the N-HLCFxs displayed nearly 100% COS and H 2 S conversion at 70 and 120 °C, respectively. Long's group synthesized N-doped mesoporous carbon by using a traditional colloidal silica nanocasting technology (Figure 3c).…”
Section: Carbon-based Materialsmentioning
confidence: 97%
“…More importantly, it presented a high regeneration performance with a sulfur capacity of 369.1 mg/g after five regeneration cycles, and S was the main product. Recently, Zhang and coauthors reported the synthesis of N-functionalized hierarchically lamellar carbon frameworks (N-HLCF-xs) via controllable carbonization of Zn zeolitic imidazolate frameworks . The N-HLCF-xs exhibited a large S BET (645–923 m 2 /g) and high density of nitrogen base sites with enhanced pyridine ratio (17.52 wt %, 59.91%).…”
Section: Selective Oxidation Of H2smentioning
confidence: 99%
See 3 more Smart Citations